Using the molecular genetics methods for studying the peculiarities of muscle activity and inherited predisposition in the sport - Drozdovska, S.B. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2013)
Analyzes of the methods used in sports genetics, and molecular genetics of muscle activity in particular are considered. The historical retrospective review of sports genetics methods was created. Contemporary level sports genetics methods were determined by the scientific literature analysis. The most common molecular genetics techniques that are used for practice and for research into sports were highlighted. It is shown that the main method, which has the greatest practical application in sport, is the method of polymerase chain reaction in various versions. These methods allow genes diagnostic and determine the genetic predisposition to perform of different kinds of physical exercises. The advantages of using these methods in sport, their features and shortcomings, prospects for further research were established.